Tailoring of recommendations to reduce serious cutaneous adverse drug reactions: a pharmacogenomics approach. (June 2017) - Tan-Koi, Wei Chuen; Sung, Cynthia; Chong, Yong Yeow; Lateef, Aisha; Pang, Shiu Ming; Vasudevan, Archana; Aw, Derrick; Lui, Nai Lee; Lee, Shan Xian; Ren, Ee Chee; Koay, Evelyn SC; Tay, Yong Kwang; et al.
The Health Sciences Authority launched a pharmacogenetics initiative in 2008 to facilitate evaluation of pharmacogenetics associations pertinent for Chinese, Malays and Indians in Singapore. The aim was to reduce the incidence and unpredictability of serious adverse drug reactions, with a focus on serious skin adverse drug reactions. This paper describes the gathering of evidence and weighing of factors that led to different genotyping recommendations for HLA-B*15:02 with carbamazepine and HLA-B*58:01 with allopurinol, despite both having strong genetic associations. Translation of pharmacogenomics at a national level requires careful deliberation of the prevalence of at-risk allele, strength of genetic associations, positive predictive value, cost–effectiveness and availability of alternative therapies. Our experience provides a perspective on translating genomic discoveries in advancing drug safety.